Influence of Leader Mindfulness on the Emotional Exhaustion of University Teachers: Resources Crossover Effect - Liu, Beini; Zhang, Zehui; Lu, Qiang (Frontiers in Psychology, 2021)
This study combined conservation of resources theory with the job demands-resources model to explore the influence of leader mindfulness on the emotional exhaustion of university teachers Using a time-lagged research design, 388 paired data sets were gathered. Multiple regression and bootstrapping were used to test each hypothesis. The results showed that first, leader mindfulness significantly reduces the emotional exhaustion of university teachers. Second, the results showed that workplace telepressure partially mediates the relationship between leader mindfulness and the emotional exhaustion of university teachers. Third, university teacher mindfulness positively moderates the relationship between leader mindfulness and workplace telepressure. Finally, the results of this study indicate that self-efficacy in managing negative emotions negatively moderates the relationship between workplace telepressure and the emotional exhaustion of university teachers. This study empirically examined the interpersonal influence of leader mindfulness and the initial resources effect of university teacher mindfulness and self-efficacy in managing negative emotions from the bilateral perspective of leaders and university teachers.